PENGARUH KONSERVATISME TERHADAP ASIMETRI INFORMASI (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR DI BEI) - Yulia, Aida (JURNAL PENDIDIKAN AKUNTANSI & KEUANGAN, 2015)
The purpose of this study was to determine the effect of accounting conservatism on information asymmetry in the annual reports of companies listed on the Indonesia Stock Exchange.Target population in this study is a manufacturing company listed on the Indonesia Stock Exchange (BEI) with year observations from 2009 to 2011 the number of companies by 23 companies.Of accounting conservatism measurements conducted on 23 companies, the population of the obtained results of all companies that meet more than one measurement assumptions of accounting conservatism with market value to book value ratio greater than 1, so that the company can be classified as a conservative company. From the test results it can be concluded that the regression coefficient of determinant (R2) value 0.240 indicates that accounting conservatism is able to affect the asymmetry of information in the annual reports of companies listed on the Indonesia Stock Exchange amounted to 24.0 percent and the remaining 76.0 percent is influenced by other variables outside of the research model. Piecemeal evidence suggests that accounting conservatism variable regression coefficient of -0.474, (β ≠ 0), meaning that in partial accounting conservatism and significant negative effect of the information asymmetry in the annual reports of companies listed on the Indonesia Stock Exchange. Refers to the requirement that the results of the study reject Ho and accept Ha.  Keywords: Accounting Conservatism and Information Asymmetry